Who owns you? : science, innovation, and the gene patent wars - Koepsell, David R. (David Richard) (Blackwell public philosophy., 2015)
The 2nd Edition of Who Owns You, David Koepsell's widely acclaimed exploration of the philosophical and legal problems of patenting human genes, is updated to reflect the most recent changes to the cultural and legal climate relating to the practice of gene patenting. Lays bare the theoretical assumptions that underpin the injustice of patents on unmodified genes Makes a unique argument for a commons-by-necessity, explaining how parts of the universe are simply not susceptible to monopoly claims Represents the only work that attempts to first define the nature of the genetic objects involved.